2019
DOI: 10.1177/1071100719839692
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Dorsal First Ray Mobility: A Topical Historical Review and Commentary

Abstract: Despite evidence that instability of the first ray (first metatarsal and medial cuneiform) alters the loading mechanics of the foot, surprisingly few studies have linked the condition with disorders of the foot. A factor limiting this research is the difficulty associated with measuring first ray mobility (FRM). To quantify dorsal FRM, clinicians and researchers have devised a variety of methods that impose a dorsally directed load, and record displacement. The methods include manual examination, radiographs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…Obviously, simplicity is an important requisite for any clinical test. Unfortunately, manual examination of the first ray ROM lacks sufficient diagnostic accuracy [8], and may be subject to great inter-rater variability. Therefore, instruments to quantify the mobility of the first ray in a valid and reliable way are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, simplicity is an important requisite for any clinical test. Unfortunately, manual examination of the first ray ROM lacks sufficient diagnostic accuracy [8], and may be subject to great inter-rater variability. Therefore, instruments to quantify the mobility of the first ray in a valid and reliable way are needed.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these instruments having been used in various studies, [11][12][13][14][15][16] they have some inconveniences such as, for example, being too complex, being large, not quantifying plantarflexion (which would be useful to compare with dorsiflexion), or not reflecting the combined movements of dorsiflexion-inversion and plantarflexion-eversion [4,17]. These are possible reasons why they are not used in daily clinical practice [8]. More simple instruments have been subsequently created aiming at solving some of the aforementioned inconveniences [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that instability in the medial column of the foot, with subsequent collapse of the arch and rotation of the hallux, may propagate hallux valgus. 6,16,23,24,34 There is a paucity of research investigating any association between pes planus and recurrence of hallux valgus following surgery. One such study reported recurrence in 40% of feet with pes planus compared with 11% of feet without pes planus (odds ratio 5.2).…”
Section: Discussionmentioning
confidence: 99%
“…To assess the fi rs ray, the subtalar joint was placed in a neutral position and the minor metatarsals are hugged with one hand and the 1st metatarsal is mobilized in dorsal fl exion and plantar fl exion. With the help of a goniometer, we assessed the greater range of motion and this will indicate the position of the metatarsal [8,12].…”
Section: First Ray Evaluationmentioning
confidence: 99%